HUKUM JIHAD DAN TERORISME: PERSPEKTIF AL-QUR’AN - Efendi Nur, H. Ma'mun (MASLAHAH (Jurnal Hukum Islam dan Perbankan Syariah), 2010)
According to the Holy Qur?an, The word 'jihad' itself is usually translated as 'struggle' or 'effort' and most broadly defined as "striving in the way of God". This can either be understood as a 'fight' against one's own spiritual shortcomings (what some have called the 'greater jihad'), or as a physical struggle for the sake of the Islamic community (the 'lesser jihad'). This article explores about jihad and terorism in the Qur?anic prspective. From this article we know that jihad is not same with terrorism. Jihad is not only war and terrorism is manifestation of violent. The essence of Islamic values, according to Qur?an that terrorism is not permitte and there is no base on the Qur?an. Jihad is one of the main duty of Muslim but terrorism is forbidden of Islamic values.